Raymond Williams and Antonio Gramsci’s contributions to adult education - Lucio-Villegas, Emilio (Adult Education Critical Issues, 2021)
This time is characterised by the policies and practices of Lifelong Learning. Against this process of dehumanisation, it could be important to ‘revisit’ some authors that enlighten us on how to recuperate an emancipatory adult education, valuable for developing critical thinking about the daily life of individuals and/or communities. In this direction, Raymond Williams and Antonio Gramsci offer us some interesting ideas. Even though they both lived in different countries and in different historic moments, they hold some common points related to a definite view of adult education. I am going to focus on three: the role of the educator, the notion of hegemony and the culture(s). In the conclusions, I will reflect on the contribution of these two thinkers to break the hegemonic view that seems to have reduced adult education to a marginalised niche. Reflecting on their contributions, mostly related to the role of the educator and the notion of culture as the core of adult education, it could be possible to recuperate the emancipatory power of adult education.